Diskursus Negara Pancasila di Kalangan Muhammadiyah - Said Romadlan (Sospol : Jurnal Sosial Politik, 2020)
This study focus on the process of understanding how Muhammadiyah is interpreted as Islamic organisation and Pancasila is as the ideology. The understanding toward Pancasila as the ideology is important because the Khalifah ideology appear to replace Pancasila. Furthermore, the drawback of globalisation which bring neoliberalism issue into society weaken the principles of Pancasila. In addition, destructive cult appears to claim that their movement/ organisation apply the most the principles of pancasila.  This study aims to investigate the strategies used by Muhammadiyah in implementing the five principle of pancasila ad the ideology. This study used hermeneutika Paul Ricoeur methodology which emphasis on the interpretation on distantiation between text and reader. The findings mentioned that the understanding about Pancasila is rely in al-Qur'an's Saba verse 15 "baldatun thayyibatun wa rabbun ghafur", (a good country is in Allah's forgiveness). In discourse analysis, this verse is interpreted by Muhammadiyah that Indonesia is a country which is used pancasila as the ideology. They believe that Indonesia is darul ahdi wa syahadah then this belief become cons discourse to against some movements to establish Khalifah Ideology.